Фенологические особенности земляники крупноплодной в условиях Камчатского края : PHENOLOGICAL FEATURES OF LARGE-FRUITED STRAWBERRY IN THE CLIMATE OF THE KAMCHATKA TERRITORY - Дахно Т.Г.; Ряховская Н.И.; Дахно О.А. (Дальневосточный аграрный вестник, 2017)
В статье представлены результаты изучения сроков наступления и продолжительности прохождения фенологических фаз у 24 сортов земляники крупноплодной различного генетического происхождения в условиях юго-восточной Камчатки. Установлено, что сорта земляники различаются между собой по времени наступления и продолжительности фенологических фаз под влиянием условий окружающей среды. По результатам фенологических наблюдений сорта распределены по срокам цветения и созревания ягод на группы: ранние, средние, поздние. : The article presents the results of the research carried out into period of the beginning and duration of the phenological stages in 24 varieties of large-fruited strawberry of different genetic origin in the southeast climates of Kamchatka. It has been found out that strawberry varieties differ in the time of the onset and duration of the phenological stages under the influence of environmental conditions. On the basis of the findings of phenological observations the varieties have been allocated in accordance with the periods of flowering and ripening of berries into the groups as follows: early, middle, late.